Caracterización del material particulado del aire ambiente en la ciudad de Loja - Regalado Contreras, Anabel Dolores (2015)
Particulate matter PM10 is one of the major air pollutants, which plays an important role in air pollution to cause adverse effects on human health associated with morbidity and mortality events in the population (Pope and Dockery, 2006) on climate change and ecosystems (IPCC, 2007). Thus, the present research aims to contribute to the acquisition of more knowledge about air pollution in the city of Loja, specifically particulate matter PM10, under this objective monitoring in the months of June to November made 2014 in the town of Loja. The equipment used was a volumetric flow controller type, located on the site of the former Central Bank of Ecuador in José A. Eguiguren between Antonio Jose de Sucre and Simon Bolivar, with UTM coordinates E 17 S 699 555 and 9558054. The results showed that concentrations of particulate matter PM10 did not exceed the maximum permissible limit is 100 μg/m3, because the arithmetic average of continuous monitoring for 24 hours, did not exceed permissible limits mentioned environmental regulations TULSMA Ecuador. Although it is noteworthy that the town of Loja where they carried out the monitoring of particulate matter PM10 is not a representative of atmospheric pollution place due to the low traffic of heavy vehicles, ground topography and lack of industries There are other areas in the city that have a high level of air pollution, so the research establishes as a proposed second goal propose strategies for monitoring, mitigation and control of particulate matter PM10, so the monitoring plan will institute the parameters for monitoring air quality in the city of Loja where the outline of how to carry out a program should monitoring of PM10 are set.